Implementation of Land and Building Acquisition Duty (BPHTB) Tax Policy at the Regional Revenue Agency of Palembang City - Akbar, Muhammad Hamka; Lionardo, Andries; Budiyanto, Muhammad Nur; Syafebri, Arrahman (LPPM Institut Pendidikan Nusantara Global, 2026)
The purpose of this research is to find out The implementation of the Acquisition Duty of Rights on Land and Buildings (BPHTB) policy serves as an essential fiscal instrument in increasing the locally generated revenue (PAD) of Palembang City. This study aims to analyze the implementation of the BPHTB policy based on Regional Regulation Number 4 of 2023 using the Thomas B. Smith implementation model, which consists of four variables: idealized policy, target group, implementing organization, and environmental factors. The research employed a qualitative approach with data collected through in-depth interviews, observation, documentation, and triangulation to ensure the validity and reliability of findings. The results indicate that Palembang City has established a strong regulatory foundation and clear Standard Operating Procedures (SOPs) to support the acceleration of BPHTB services. However, the implementation still faces several challenges, including digital system disruptions, inconsistencies in taxpayer-submitted data, a high verification workload, and dependence on specific officials for document authorization. On the taxpayers’ side, low administrative and digital literacy, the tendency to report transaction values below market price, and limited understanding of BPHTB requirements often hinder the service process. From the implementing organization’s perspective, variations in staff competence, suboptimal internal coordination, and inconsistent service responses remain significant obstacles. Meanwhile, environmental factors such as fluctuations in property market prices, the economic capacity of taxpayers, and coordination with PPAT, the National Land Agency (BPN), and banking institutions also influence the effectiveness of implementation.This study concludes that the success of BPHTB policy implementation is strongly determined by the synergy between a solid regulatory framework, technological readiness, human resource quality, data accuracy, and the level of taxpayer participation and compliance. Therefore, the study recommends strengthening digital governance, enhancing the capacity of public officials, optimizing inter-agency coordination, and improving socialization strategies for taxpayers to enhance the overall effectiveness of BPHTB implementation in Palembang City.